North Atlantic Pleustidae (Crustacea, Amphipoda) with a focus on cold-water coral associations - Anne-Nina Lörz; Anne Helene S. Tandberg (European Journal of Taxonomy)
While amphipods are key players in any marine environment, hardly anything is known about their cold-water coral associations. As part of Remotely Operated Vehicle-examinations of cold-water corals from the Reykjanes Ridge southwest of Iceland, we sampled several species of the amphipod family Pleustidae, often hundreds of specimens from single corals. The live camera sampling allowed an investigation of the host specificy of the amphipods and a detailed taxonomic investigation including in situ images. Several species new to science were discovered; here, we describe Neopleustes schwentneri sp. nov. and Stenopleustes jeskulkeae sp. nov. in detail. An extensive documentation of morphological details via Scanning Electron Microscope Images gives unprecedented insights into the diversity of Pleustidae in association with cold-water corals.